The Information Technology Challenge and Library and Information Work in Ghana - Entsua-Mensah, Clement (Ghana Library Journal, 1989)
Developments in microelectronic technology and telecommunications facilities have had considerable impact on library work in some parts of the world. Unfortunately for us in Ghana, we are yet to avail ourselves of these developments. Considerable progress has been made in the area of information handling, and today the combination of computer and communication equipment has overcome time and distance as major obstacles to gaining access to information stored in remote databases. The challenges posed bythese developments to third world countries are many. The paper, therefore, discusses some of the propects and limitations involved in introducting information technology (IT) into libraries in the country.